ACTIONABLE CULTURAL RESOURCES FOR SUSTAINABLE LOCAL TOURISM DEVELOPMENT – MERITS OF DIGITAL SUPPORT SYSTEMS - Peter Nijkamp; Karima Kourtit; Yneke Van Iersel; Henk Scholten; Antonia Gravagnuolo (Cadernos CEPEC)
Sustainable tourism development is a major policy challenge for many cities, regions or countries. This paper describes various novel analytical ingredients to ensure a consistent and professional policy strategy in tourism destinations. In all cases, reliable and accessible data are necessary for an actionable tourism policy. In the present study advanced digital support systems for cultural resource-use in local tourism strategies are presented. The paper uses the region of South-Limburg in the Netherlands as a data-driven testcase and as a cultural tourism showcase for demonstrating the great potential of digital twins as digital visual policy and participation tools for co-creative local sustainable tourism development